Review: Analysis of Protein Levels in Stunted Childern in Southern Kalimantan - Tukat, Cecilia Luvinska Christine (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2025)
Stunting is a global problem that causes children to grow and develop shorter than their peers. Many factors influence this, including protein. Thus, the purpose of the study was to determine whether there is a relationship between protein levels and the incidence of stunting in children in South Kalimantan. The method that can be done is to collect data through a literature review from several journals. Based on the data obtained, South Kalimantan Province has a stunting prevalence of 11.9%. Then, based on the research, there is a relationship between protein levels and the incidence of stunting in children.